Catalyst-free transesterification vitrimers: activation via α-difluoroesters. Issue 18 (14th April 2022) - Cuminet, Florian; Berne, Dimitri; Lemouzy, Sébastien; Dantras, Éric; Joly-Duhamel, Christine; Caillol, Sylvain; Leclerc, Éric; Ladmiral, Vincent
Abstract : Transesterification vitrimers often require high catalyst loadings to prepare 3D networks reprocessable at moderately high temperature. Abstract : Transesterification vitrimers often require high catalyst loadings to achieve 3D networks reprocessable at moderately high temperature. The addition of an activating group close to the ester bonds allows to synthesize catalyst-free transesterification vitrimers. Here, we unveil the effect of the α-difluoromethylene group as a novel activating group for such materials. Fluorine features exceptional properties, in particular a strong electronegativity enabling CF2 groups to activate the epoxy-acid polymerization, and more interestingly also the transesterification reaction on adjacent esters. Consequently, this fluorinated group affords the easy synthesis of a highly crosslinked reprocessable material that do not require any metallic or organic catalyst. This vitrimer is endowed with advantageous reprocessing abilities and underwent 10 consecutive cycles without loss of mechanical properties. In brief, the vitrimer combines durability, recyclability and is catalyst-free. This discovery is one step further towards recyclable greener polymers.